Implikasi Pemberdayaan Zakat Produktif Terhadap Mustahik Melalui Indikator Perbaikan Pendapatan, Perbaikan Hidup, dan Perbaikan Usaha : Studi Kasus Yayasan Dana Sosial Al Falah Malang - Muhammad Wifaqul Azmi; Ajeng Kartika Galuh (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Poverty is one of the complex issues posing a serious threat for developing countries such as Indonesia. With its high potential of zakat revenue, which can serve as an instrument of economic distribution and equality as well as socio-economic function driver, this nation is expected to be able to reduce disparity and foster self-sufficiency among its people. The objective of this research is to analyze the impacts of productive zakat empowerment through the Independent Business Group (KUM) program by Yayasan Dana Sosial Al-Falah (YDSF) of Malang on the wellbeing of the zakat beneficiaries, the mustahik. The foci of this research are business improvement, income improvement, and life improvement. The primary data of this qualitative descriptive case study was acquired via in-depth interviews, observations, and document studies, and the secondary data was harvested from library research. The subject consists of nine beneficiaries of the program from various business fields. The results of the analysis indicate that the program increased the beneficiaries’ business capacity through business capital aid, training, and managerial and spiritual assistance. Such impact is observable from increases in the beneficiaries’ average income, ability to fulfill basic needs, growing business, and overall improvements in material and non-material life quality. However, most of them are still infaq providers (munfiq) and small charity givers (mushoddiq), who have not entirely transformed into zakat payers (muzakki). This study highlights the importance of optimizing productive zakat management oriented toward sustainability and long-term mentoring to help mustahik transforming into economically independent people. Therefore, management system improvement and monitoring as well as more massive and sustainable strategies are crucial in order to ensure that productive zakat functions as a strategic instrument for poverty eradication and people’s economic empowerment.